2020
DOI: 10.1007/s10796-020-10029-0
|View full text |Cite|
|
Sign up to set email alerts
|

Modelling the Asymmetrical Relationships between Digitalisation and Sustainable Competitiveness: A Cross-Country Configurational Analysis

Abstract: Sustainable competitiveness (SC) encourages nations not only to meet the needs of the current generation but also to sustain or even expand national wealth in the future without depleting natural and social capital. Drawing on complexity theory, we used a configurational approach to identify under what necessary and sufficient conditions, digitalisation contributes to achieve higher SC. Shifting attention from net effects to configuration analysis improves our understanding of cross-national differences in sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 91 publications
2
31
0
Order By: Relevance
“…Digital transformation is shaping the business environments of contemporary companies and Big Data analytics and digital business ecosystems are providing increasingly new possibilities for companies to develop their businesses; therefore, companies need to be able to respond to the changes and understand the possibilities provided by increased digitalization (Delgosha et al 2020;Mikalef et al 2020;Pappas et al 2018). Companies need to find ways to exploit innovation in digitalizing business environments (Bednar and Welch 2019;Mikalef et al 2018) and to understand the role of different types of capabilities as a part of these activities (Mikalef et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital transformation is shaping the business environments of contemporary companies and Big Data analytics and digital business ecosystems are providing increasingly new possibilities for companies to develop their businesses; therefore, companies need to be able to respond to the changes and understand the possibilities provided by increased digitalization (Delgosha et al 2020;Mikalef et al 2020;Pappas et al 2018). Companies need to find ways to exploit innovation in digitalizing business environments (Bednar and Welch 2019;Mikalef et al 2018) and to understand the role of different types of capabilities as a part of these activities (Mikalef et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As digital transformation is shaping the business environments of contemporary companies, companies need the adjust their operations and find ways to respond to the changes. To operate in increasingly digitalized business environments, and as a part of the digital ecosystems (Delgosha et al 2020;Pappas et al 2018), companies need to not only find innovations and innovative ways to change their businesses but also develop capabilities to exploit innovation in changing surroundings. Further, Mikalef et al (2020), argued that to derive value from the growing opportunities of digitalization, such as big data, companies need to develop the organizational capacity to recognize how their businesses can benefit from data-driven insight, as well as develop capabilities to implement these recognized possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…The digital revolution has radically transformed economies and help societies to develop new mechanisms for human wellbeing, national wealth, natural resources, and sustainability. 60 , 61 Drawing on the complexity theory, Delgosha et al 33 argued that ICT usage, adoption, capabilities, and infrastructures encourage countries to achieve sustainable competitiveness without compromising social and natural capital. Using a global panel data of 107 countries, Laidroo and Avarmaa 62 revealed that FinTech establishment intensity is stronger in countries with greater ICT readiness and service clusters.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“… 31 Thereby both ICT and financial development support economies to achieve sustainable competitiveness. 32 , 33 …”
Section: Introductionmentioning
confidence: 99%
“…This enables fsQCA as a tool to recognise the diversity and heterogeneity of cases, in terms of their causally relevant conditions and contexts, by allowing cases to be compared as configurations (Fiss, 2011). As an established analytical tool for investigating the configurational nature of conditions (Delgosha et al, 2020;Fiss, 2011;Pappas, 2018;Pappas et al, 2020) fsQCA enabled an identification of the combinations of knowledge transfer conditions that led to success in ecosystem contexts.…”
Section: Fsqcamentioning
confidence: 99%